Analisis Akuntabilitas Pengelolaan Keuangan Masjid Melalui Pendekatan Fenomenologi (Studi Kasus Pada 3 Masjid Di Kota Medan) - Dhea Natasya S; Tri Inda Fadhila Rahma; Nur Fadhilah Ahmad Hasibuan (LPPM Universitas Labuhanbatu, 2026)
This study aims to analyze accountability in financial management implemented in 3 mosques in Medan City, namely the Al-Jihad Mosque in Medan Baru, the Abidin Mosque in Medan Maimun and the Great Miftahul Iman Mosque in Medan Denai. This research is a qualitative research using a phenomenological approach. The techniques used in data collection were observation, interviews and documents by looking directly at the financial reports presented by mosque administrators. The results of this study indicate that the financial manager of the Al-Jihad Medan Baru mosque makes two types of financial reports, namely simple financial reports in the form of recording receipts and disbursements of cash funds and financial reports in accordance with ISAK 35. The financial manager of the Abidin Medan Maimun mosque makes financial reports that are not in accordance with ISAK 35 by making simple reports in the form of mosque cash receipts and disbursements and the financial manager of the Raya Miftahul Iman Medan Denai mosque also only makes simple records in making mosque financial reports. Reporting as a form of accountability is carried out by the manager before carrying out Friday prayers, but the manager only mentions the amount of income and expenses and the manager presents detailed financial reports to the mosque's mading.